Contribution of mascolive veterinary clinic to animal and public health - Espinosa-Ruiz, César A. (2025)
The veterinary medicine service comprises the set of preventive, assistance and veterinary health activities and measures aimed at guaranteeing the health of animals, as well as guaranteeing the health and welfare of humans in the country, according to Decree Law No. 137/1993 on Veterinary Medicine from Cuba. The research shows how in the “Mascolive” Veterinary Clinic observes national and international legislation in its services, contributing to the protection of animal and public health in the municipality of Playa and other municipalities of Havana. In its assistance, preventive activities, training of tutors and the community, and interrelation with public health authorities, education and the general public, “Mascolive” contributes to reduce the risks of zoonoses in the human-animal-environment interface, to prevent and control diseases and to reduce antimicrobial resistance, with the collaborative, transdisciplinary and multisectoral work of the One Health approach.